2020
DOI: 10.1002/ejhf.1754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exergaming on exercise capacity in patients with heart failure: results of an international multicentre randomized controlled trial

Abstract: Aims Exergaming is a new tool to increase physical activity. This study aimed to determine the effects of access to a home‐based exergame (Nintendo Wii) in patients with heart failure (HF) on exercise capacity, self‐reported physical activity and patient‐reported outcome measures. Methods and results We enrolled 605 HF patients in New York Heart Association functional class I–IV, independent of ejection fraction, in an international multicentre randomized controlled trial. Patients were randomized to exergame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 51 publications
(130 citation statements)
references
References 40 publications
1
76
0
1
Order By: Relevance
“…However, the authors underlined that this type of program is feasible and safe. 25 In addition, because 36% of the patients report being inactive at baseline and this proportion did not change after the follow-up, the authors emphasize the importance of remote coaching and the necessity to study specifically remote motivational strategies. 25 To summarize, compared with conventional center-based CR, recent studies and meta-analyses suggest that telerehabilitation could be (1) as effective on improving the _ VO 2 peak, (2) less costly, (3) safe, and (4) more effective in terms of maintenance of an active lifestyle in the medium-term.…”
Section: Exergames In Crmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the authors underlined that this type of program is feasible and safe. 25 In addition, because 36% of the patients report being inactive at baseline and this proportion did not change after the follow-up, the authors emphasize the importance of remote coaching and the necessity to study specifically remote motivational strategies. 25 To summarize, compared with conventional center-based CR, recent studies and meta-analyses suggest that telerehabilitation could be (1) as effective on improving the _ VO 2 peak, (2) less costly, (3) safe, and (4) more effective in terms of maintenance of an active lifestyle in the medium-term.…”
Section: Exergames In Crmentioning
confidence: 99%
“…25 In addition, because 36% of the patients report being inactive at baseline and this proportion did not change after the follow-up, the authors emphasize the importance of remote coaching and the necessity to study specifically remote motivational strategies. 25 To summarize, compared with conventional center-based CR, recent studies and meta-analyses suggest that telerehabilitation could be (1) as effective on improving the _ VO 2 peak, (2) less costly, (3) safe, and (4) more effective in terms of maintenance of an active lifestyle in the medium-term. 19,[26][27][28][29][30][31] Regarding mortality, cardiovascular risk factors, and physical activity volume, Dalal et al demonstrated in 1938 cardiac patients that there was no difference between home-based and center-based CR programs.…”
Section: Exergames In Crmentioning
confidence: 99%
See 1 more Smart Citation
“…The details and primary outcomes of that study have been published elsewhere. 23,24 The exclusion criteria were 'Unable to use the Nintendo Wii due to visual impairment (see a TV screen at a distance of 3 m), hearing impairment (the patient is not able to communicate by telephone), cognitive impairment (assessed by a HF nurse or cardiologist), or motor impairment (the patient should be able to swing his arm at least 10 times in a row)', 'Unable to fill in data collection material', and 'life expectancy shorter than 6 months'. This study used data collected from patients in the HF-Wii study who had provided accelerometer data measurements (n = 106).…”
Section: Methodsmentioning
confidence: 99%
“…A solution to promote physical activity for LVAD supported patients can be by telerehabilitation sessions, exergaming or by sending video instructions given by the local physiotherapist known to the group of LVAD supported patients (13,14). This can be preferred above 'standard online video instructions' since the patients see a familiar face, are familiar with his/her instructions and by that, not only improve their adherence to physical activity but also decrease their feeling of isolation.…”
Section: Solutions and Practical Tipsmentioning
confidence: 99%